MSME LIVING STRATEGY AND DEVELOPMENT STRATEGY IN THE TIME OF THE COVID-19 PANDEMIC IN JAYAPURA CITY - Ratang, Sarlota (Advances in Social Sciences Research Journal, 2021)
This study aims to determine and analyze the survival and development strategies of MSMEs in Jayapura City which were implemented due to the impact of the Covid-19 pandemic. The research method used is descriptive qualitative method. The results obtained from this study indicate that there are many negative impacts that affect MSME actors during the Covid-19 pandemic, meanwhile there are many survival strategies for business actors but the most that can make them survive is to do e-commerce or sell products online, digital marketing and product repair and improvement. For the development of MSMEs, what can be done is to improve the quality of human resources, develop knowledge of financial literacy and expand market access.